Immunomodulatory, gastroprotective and wound healing potential of Malaysian medicinal plants (phaleria macrocarpa and tinospora crispa) / Walaa Najm Abood - Abood, Walaa Najm (2014)

(untitled)
Phaleria macrocarpa (Scheff.) Boerl and Tinospora crispa (L.) are considered im-portant traditional medicines commonly used in Malaysia and South East Asian coun-tries. In this study, the ethanol extracts of P. macrocarpa fruit and T. crispa stems were evaluated for their immunomodulatory, gastroprotective and wound healing potential. In addition, acute toxicity and antioxidant activities were investigated using DPPH and FRAP values as well as the total phenolic and total flavonoid contents. The findings of this study suggest that the high antioxidant activity that was found in P. macrocarpa and T. crispa was due to the high-level of phenol and flavonoid content. According to the results of the acute toxicity study, P. macrocarpa and T. crispa should both be as-signed to the lowest toxicity class. The potential protective effects of P. macrocarpa and T. crispa on rat gastric mucosal injury induced by ethanol and to clarify the roles of gastrin, pepsin, prostaglandinE2 (PGE2), superoxide dismutase (SOD), catalase (CAT), malondialdehyde (MDA), and inflammatory mediators; transforming growth factor-beta (TGF-β1) and tumor necrosis factor alpha (TNF-α). Results showed signifi-cant ulcer protective effects through the reduction of the ulcer area by a significant ele-vation of gastric juice pH and an increase of mucus production, as well as a significant increase in the levels of inflammatory mediators PGE2 and TGF-β1 and a decrease in TNF-α. In addition, the groups pretreated with P. macrocarpa and T. crispa eehibited increased significant activity of SOD and CAT but significantly reduced MDA, gastrin and pepsin levels . For wound healing potential, groups were topically treated with the P. macrocarpa and T. crispa extracts daily for 15 days, and wound healing in this group was significantly accelerated compared with the control group. This result was attribut-ed to a significant increase in TGF-β1, SOD and CAT, and a significant decrease in the iii TNF-α and MDA level in the treated groups. Besides, there was also an effect on the apoptosis process by regulating the expression of BAX and BCL2 genes. To achieve the immunomodulatory effect of P.macrocarpa, T. crispa and their isolated fractions in ac-tivated macrophages to release cytokines as IFN-γ, IL-6 and IL-8, a RAW264.7 macro-phage cell line was used to determine immunomodulatory activity by investigating in-tracellular cytokine expression. The results showed that there is an immunomodulatory effect of P.macrocarpa and T. crispa and their isolated fractions by increasing RAW 264.7 macrophage cell proliferation in a dose dependent manner, and significant induc-ing of the intracellular expression of cytokines IFN-γ, IL-6 and IL-8. In conclusion, our results prove that P. macrocarpa and T. crispa have a significant immunomodulatory effect as immunostimulators, giving protective effects against ethanol-induced gastric ulcers. These extracts also possess wound-healing capability by improving the activity of endogenous antioxidant enzymes and preventing free radical-mediated tissue injury besides significantly stimulating the inflammatory mediators, which also, play an im-portant role in the inflammation process, apoptosis regulation, and the remodeling phase in wound healing.